The Role of Qawāʿid fiqhiyyah in Addressing Contemporary Legal Issues - Wildan Miftahussurur; Muhammad Fauzinudin Faiz (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2026)
This article examines the role of qawāʿid fiqhiyyah (Islamic legal maxims) as a methodological framework for addressing contemporary legal issues in Islamic law. Employing a qualitative normative-analytical approach, the study analyzes classical juridical texts and contemporary Islamic legal scholarship to explore how legal maxims function in modern legal reasoning. The findings demonstrate that qawāʿid fiqhiyyah operate not merely as doctrinal summaries, but as active instruments that structure juristic reasoning, mediate between normative sources and social realities, and guide legal judgment in contexts marked by complexity and uncertainty. The analysis further reveals that legal maxims play a crucial role in operationalizing the objectives of Islamic law (maqāṣid al-sharīʿah), particularly in areas related to legal certainty, harm prevention, facilitation, and contextual adaptation. By bridging classical doctrine and contemporary socio-legal challenges, qawāʿid fiqhiyyah enable Islamic law to maintain methodological coherence while remaining responsive to change. This study argues that the continued relevance of Islamic law in the modern era depends not on normative rupture, but on the reactivation of its internal juristic methodologies, with legal maxims serving as one of its most robust and adaptable tools.